Production cost and income analysis vegetable business “Prosperous” in the Eligibility of Andasan Ulinnorth - Gusti Marliani; Peby Pebriyanti (Keynesia : International Journal of Economy and Business, 2022)
Analysis of Production Costs and Income in the Makmur Sejahtera Vegetable Farming Group in North Landasan Ulin Village. Under the guidance of: Gusti Marliani, SE., ME and Haris Irawan, SE, M.Sc. Thesis for Undergraduate Development Economics Study Program, Faculty of Economics, Achmad Yani University Banjarmasin in 2022. This study aims to determine the production costs and income of the Makmur Sejahtera Vegetable Farming Group in North Landasan Ulin Village. Data collection used for direct interview techniques with respondents, namely group leaders and members of the prosperous and prosperous vegetable farming group regarding production costs. Determination of respondents is done intentionally, namely with one group leader and other members who are farming.The results showed that the total cost incurred by the Makmur Sejahtera Vegetable Farming Group was Rp.128,746,000 consisting of fixed costs and variable costs. The income obtained by the Makmur Sejahtera Vegetable Farming Group is Rp. 17,029,000.